PEMBERDAYAAN NELAYAN DENGAN KONSEP PERIKANAN TANGKAP DI DESA WATUONDO KECAMATAN WAWONII TIMUR LAUT KABUPATEN KONAWE KEPULAUAN - Dja'wa, Asrianti; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
Fishing is decreasing due to the lack of support for the ship's equipment, such as still using a manual ship engine (crank), a manual compass that is difficult to detect direction, ship electricity using the ship's main engine. This is what prompted the Management Study Program Team of the Islamic Faculty of Economics and Business, Muhammadiyah University of Kendari to do community service on the topic of Empowering fishermen through the development of capture fisheries in Watuondo Village. The method used in this research is training and outreach. The results obtained were that there were 30 participants who attended, namely 15 people from large fishermen groups and 11 people from small fishermen or around 99 percent who attended, meaning that this activity was successfully carried out where the target attendance was above 80 percent. The socialization and training carried out has an impact which increases the understanding and knowledge of fishermen and will increase their income. However, there are some fishermen who must be assisted and assisted with incentives.